ETNOMATEMATIKA MANDAR: EKSPLORASI KONSEP GEOMETRI PADA RAWANA MANDAR - Nur Alim Subur; Diva Ummi Kalsum Wijaya; Hariati; Nadira; Siti Rahma; Karisa Tawang; Amran Yahya (TRANSFORMASI, 2026)
This study aims to explore geometry concepts embedded in Mandar Rawana and examine their implementation in mathematics learning. A qualitative approach with an ethnographic method was employed. The research was conducted in Renggeang Village, Limboro District, Polewali Mandar Regency, West Sulawesi. The research informant consisted of one artisan and a rawana player selected purposively based on their active involvement in the making and playing of rawana. Data were collected through observation, interviews, and documentation, with source triangulation applied to ensure data validity. The findings reveal that Mandar Rawana contains four geometry concepts: circle and its elements on the surface of the skin and wooden frame, arc and chord in the arrangement of fastening nails along the frame edge, symmetry in the balanced shape of the Rawana from all directions, and similarity in two Rawana units of different sizes. All four concepts can be implemented in school mathematics learning through direct exploration using Rawana as a concrete and contextual medium rooted in local wisdom. Theoretically, these findings reinforce ethnomathematics studies demonstrating that local cultural artifacts represent mathematical concepts. Practically, Mandar Rawana has strong potential as a contextual and meaningful geometry learning medium for students.